ANALISIS KASUS ILLEGAL FISHING OLEH WARGA NEGARA CHINA DI MERAUKE MENURUT KEJAHATAN TRANSNASIONAL - Bagus Prayitno, Eka; Mega, Aryanti; Mustika Wardani, Sri (JURNAL DWIJA KUSUMA, 2024)
Indonesia is an archipelago country which consists of 17.504 islands, and around two third the country which is 6.400.000 km² is sea water. Indonesia has an enormous potential fisheries based on the data from the Ministry of Fisheries and Maritime Affairs as it is stated in Kepmen KP No.19 / 2022 that the Potential of Fisheries Resource Estimation was predicted as much as 12,01 million tons per year with JTB 8,6 million tons per year. The estimation is divided into nine groups of fisheries resources, they are demersal fish, reef fish, small pelagic, the, shrimp, lobster, rajungan, crab and large pelagic. The extensive region of indonesia which does not have sufficient supervision become captivating resource for foreign country to exercise an act of illegal fishing. This research used normative juridical law research. The authors will analyze the existing regulations with sanctions using examples of cases that have occurred. Is the regulation fixed enough to present the effect on the perpetrators of illegal fishing crimes. The primary data comes from the law regulations and court rulings as well as the secondary data which was brought from books, news and journals. The research approach methods are law approach and analysis of the court's verdict, as well as qualitative descriptive data analysis. The datas and documents were obtained from library research which had been analyzed in a qualitative descriptive method. Indonesia already has a law of fishing which has been a guideline for prosecuting fisheries criminals, they are Undang-Undang Nomor 45 tahun 2009 on changes from Undang Nomor 31 Tahun 2004 about fisheries.This writing will examine the effectiveness of the sanctions by analyzing the cases committed by Chinese citizens in Marauke. The results from this research will help the understanding of the needs for firmness in law enforcement in order to generate deterrent effects for criminals.